Enhancement of anaerobic waste activated sludge digestion by microwave pretreatment - Eskicioglu, Cigdem (University of Ottawa (Canada), 2006)
Improvement of biodegradability of waste activated sludge (WAS) depends on enhanced disintegration of the floc structure of sludge and increasing the accessibility to both intracellular (within the microbial cell) and extracellular (within the polymeric network) materials before WAS is sent to anaerobic digesters. This study proposes microwave (MW) technology as a new and an alternative pretreatment method to disintegrate the floc structure of secondary sludge, to enhance the hydrolysis and to improve the anaerobic digestion of WAS in comparison to existing pretreatment methods such as, chemical, mechanical and conventional heating (CH) techniques. In the first stage of the study, the effects of MW pretreatment on disintegration and hydrolysis of WAS by soluble chemical oxygen demand (COD), soluble protein, soluble sugar and nucleic acid leakage detection experiments were investigated. The effects of three variables [MW temperature (T), MW intensity (I), WAS concentration (C)] and the effects of four variables [T, I, C and volume percentage of WAS pretreated (PT)] were investigated on WAS solubilization and biogas production in two multilevel factorial statistical designs containing 24 solubilization runs and 54 mesophilic batch reactors, respectively. In a low temperature range (50-96°C) using a household type (1250 W, 2450 MHz) MW oven, pretreated WAS samples resulted in 3.6 +/- 0.6 and 3.2 +/- 0.1 fold increases in soluble COD/total COD ratios at high [5.4% total solid (TS), w/w] and low (1.4% TS, w/w) sludge concentrations, respectively. WAS, pretreated to 96°C, produced the greatest improvement in biogas production with 15 +/- 0.5 and 20 +/- 0.3% increases over the controls (unpretreated) after 19 d of digestion at low and high WAS concentrations. In the second stage of the study, two different pretreatment temperatures (50 and 96°C) were further tested in a total of 10 semi-continuous digesters at sludge retention times (SRTs) of 5, 10 and 20 d. Digesters using CH WAS were also run to investigate thermal and athermal effects of MW pretreatment. In general, incremental increases in total solid (TS), volatile solids (VS) and total COD removal efficiency of pretreated digesters compared to controls dramatically increased as SRT was gradually shortened from 20 to 10 to 5 d. WAS pretreated to 96°C by MW and CH achieved 29 and 32% higher TS and 23 and 26% higher VS removal efficiencies compared to controls at SRT of 5 d, while similar reactors at SRT of 20 d had only 16% higher TS and 11 and 12% higher VS removals than those of controls, respectively. Ultrafiltration (UF) was also used to characterize the soluble molecular weight (Mw) distributions of control, CH and MW irradiated WAS at 96°C. Soluble CODs of CH and MW irradiated WAS were 361 +/- 45 and 143 +/- 34% higher and resulted in 475 +/- 3 and 211 +/- 2% higher cumulative biogas productions relative to the control at the end of 23 days of mesophilic batch anaerobic digestion, respectively. Depending on the Mw fraction, the range of substrate volumetric utilization rate increases from anaerobic digesters was between 94-184% for the CH and 26-113% for the MW compared to the control for the first 9 days of the digestion. Digesters treating high Mw materials (Mw > 300 kDa) resulted in smaller first-order biodegradation rate constants, k, indicating that microorganisms require a longer time to utilize high Mw fractions which are most likely the cell wall fragments and exopolymers. MW studies under the boiling point (100°C at 1 atm) have promised a significant potential to disintegrate the floc structure and to enhance the hydrolysis and biodegradability of WAS in full-scale digesters.
Keywords: Engineering, Sanitary and Municipal.; Engineering, Environmental.